Mycotoxins in cereals and pulses harvested in Latvia by nanoLC-Orbitrap MS. Issue 2 (3rd April 2021) - Reinholds, Ingars; Jansons, Martins; Fedorenko, Deniss; Pugajeva, Iveta; Zute, Sanita; Bartkiene, Elena; Bartkevics, Vadims
ABSTRACT: Twenty-seven mycotoxins in unprocessed cereals ( n = 110) and pulses ( n = 23) harvested in Latvia were analysed by nanoflow liquid chromatography combined with Orbitrap high-resolution mass spectrometry. One or more mycotoxins were found in 99% of the cereals and 78% of the pulses. Deoxynivalenol, zearalenone and T-2 and HT-2 toxins were prevalent in 9 to 86% of the cereals, mostly below their maximum levels as set by the European regulations. Non-regulated type A and B trichothecenes were prevalent in 5 to 87% of the cereals, at concentrations of 0.27–83 µg kg −1 and 1.7–4, 781 µg kg −1, respectively. Quantification of emerging mycotoxins was also provided. Enniatins were detected in 94% of the cereals (3.5–2, 073 µg kg −1 ) and 13% of the pulses (4.4–17 µg kg −1 ). Alternaria toxins were prevalent in 94% of the cereals at concentrations of 0.72–307 µg kg −1 and in 39% of the pulses at 0.69–10 µg kg −1 .